Towards regionalization of the chondrichthyan fauna of the Southwest Atlantic: a spatial framework for conservation planning - Sabadin, David Ezequiel (2020)
Biogeographic regionalization identifies natural species assemblages of a given region. In this study, the geographic distribution of chondrichthyan species richness and species assemblages for the Southwest Atlantic were identified. The geographic distribution of 103 chondrichthyans was estimated through modelling. Based on the obtained binary maps, the distribution of chondrichthyan richness was obtained at four taxonomic levels: class Chondrichthyes (chondrichthyans), subclass Holocephali (chimaeras), division Selachii (sharks), and division Batomorphi (batoids). The continental shelf off Uruguay and southern Brazil presented the highest levels of chondrichthyan richness, and a smaller peak was found in El Rincón (northern Argentina). Shark richness concentrated mainly off Lagoa dos Patos (southern Brazil). Batoid richness was maximal off Uruguay and northern Argentina, including modes in El Rincón, San Jorge Gulf, and slope of the Argentinean shelf. Classification analyses revealed the presence of a hierarchical regionalization, with three main and six minor assemblages. Main assemblages are hierarchically identifiable as provinces and minor ones as ecoregions or districts. Two of the main assemblages correspond with the Argentinean and Magellanic Provinces; the third one is identified here for the first time, the Patagonian Slope Province. This regionalization provides the basis for the design of protected area networks for conservation or management purposes.